A randomized, double-blind, placebo-controlled trial assessing the efficacy of S66913 in patients with paroxysmal atrial fibrillation. Issue 1 (23rd July 2018) - Camm, A John; Dorian, Paul; Hohnloser, Stefan H; Kowey, Peter R; Tyl, Benoît; Ni, Yongbin; Vandzhura, Victoria; Maison-Blanche, Pierre; de Melis, Mirko; Sanders, Prashanthan
Abstract: Aims: Antiarrhythmic drugs (AADs) for the treatment of atrial fibrillation (AF) are associated with limited efficacy and adverse effects. Inhibition of the atrial current IKur, absent from the ventricle, is expected to be antiarrhythmic, without adverse cardiac effects, particularly ventricular pro-arrhythmic effects. Methods and results: A randomized clinical trial in symptomatic paroxysmal AF patients being considered for ablation. The primary endpoint was AF burden (AFB) as measured by insertable continuous monitoring (ICM) devices. Screened patients had an ICM implanted and were included if AFB was between 1% and 70% after 4 weeks of recording. They were randomly allocated to 4-week treatment of a selective IKur inhibitor S66913 (5 mg, 25 mg, or 100 mg orally per day) or placebo. The study was to enroll 160 patients. The study was terminated prematurely, due to non-study related preclinical safety concerns, after 58 patients had been enrolled. The median AFB ranged from 4.3% to 10.3% at baseline in the four treatment groups. S66913 had no significant effect on AFB or on AFB plus atrial tachycardia (AT) burden, at any dosage; nor on any secondary endpoints including the number and duration of AT or AF episodes, and symptoms. The drug was well tolerated with no safety concern during the treatment or the extended clinical follow-up. Conclusions: DIAGRAF-IKUR was the first study to show that using ICM to assess the effect of an AAD is feasible. The selective IKur inhibitor S66913 was safe but had no clinically meaningful effect at the time of early termination of the study.